Development of Pineapple Microsatellite Markers and Germplasm Genetic Diversity Analysis. (19th August 2013) - Feng, Suping; Tong, Helin; Chen, You; Wang, Jingyi; Chen, Yeyuan; Sun, Guangming; He, Junhu; Wu, Yaoting
Abstract : Two methods were used to develop pineapple microsatellite markers. Genomic library-based SSR development: using selectively amplified microsatellite assay, 86 sequences were generated from pineapple genomic library. 91 (96.8%) of the 94 Simple Sequence Repeat (SSR) loci were dinucleotide repeats (39 AC/GT repeats and 52 GA/TC repeats, accounting for 42.9% and 57.1%, resp.), and the other three were mononucleotide repeats. Thirty-six pairs of SSR primers were designed; 24 of them generated clear bands of expected sizes, and 13 of them showed polymorphism. EST-based SSR development: 5659 pineapple EST sequences obtained from NCBI were analyzed; among 1397 nonredundant EST sequences, 843 were found containing 1110 SSR loci (217 of them contained more than one SSR locus). Frequency of SSRs in pineapple EST sequences is 1SSR/3.73 kb, and 44 types were found. Mononucleotide, dinucleotide, and trinucleotide repeats dominate, accounting for 95.6% in total. AG/CT and AGC/GCT were the dominant type of dinucleotide and trinucleotide repeats, accounting for 83.5% and 24.1%, respectively. Thirty pairs of primers were designed for each of randomly selected 30 sequences; 26 of them generated clear and reproducible bands, and 22 of them showed polymorphism. Eighteen pairs of primers obtained by the one or the other of the two methods above that showed polymorphism were selected to carry out germplasm genetic diversity analysis for 48 breeds of pineapple; similarity coefficients of these breeds were between 0.59 and 1.00, and they can be divided into four groups accordingly. Amplification products of five SSR markers were extracted and sequenced, corresponding repeat loci were found and locus mutations are mainly in copy number of repeats and base mutations in the flanking region.